Triple Boron-Cored Chromophores Bearing Discotic 5,11,17-Triazatrinaphthylene-Based Ligands - Qiu, Feng; Zhang, Fan; Tang, Ruizhi; Fu, Yubin; Wang, Xinyang; Han, Sheng; Zhuang, Xiaodong; Feng, Xinliang (Organic Letters, 2016)
A series of novel chromophores fused with multiple boron cores have been successfully synthesized by the complexation of three difluoroboryl or diphenylboryl at the periphery of 5,11,17-triazatrinaphthylene derivative ligands. Their sterically congested molecular scaffolds with expanded φ-conjugated discotic backbones render them with unique electronic properties including large Stokes shifts, tunable electrochemical behaviors, and low-lying LUMO energy levels up to -3.18 eV.
CRIS-Team Scopus Importer:2023-03-20